MENINGKATKAN KEMAMPUAN MENCUCI PAKAIAN MELALUI ANALISIS TUGAS PADA ANAK TUNAGRAHITA SEDANG - Sari Kurniawati (Jurnal Penelitian Pendidikan Khusus, 2015)
This research was conducted based on the problem found in the field indicating that a student with light mental retardation X got problem to wash his clothes. The purpouse of this  research was to increase the student’s ability to wash clothes though task analysis in class IV C1 of SLB Fanredha Padang. This was a Single Subject Research which used  A-B design. A condition (baseline condition) was the  initial contion showing  the student’s ability to wash  clothes before the treatment given. B condition ( intervention condition) was the  condition through which the task analysis was applied. The result of the research indicated that the ability of the studen with light mental reterdation to wash clothes increased after the  task analysis given. In the  baseline condition, six observasions were  conducted. In this  condition the highest score was 35%. In the intervention condition that consited of ten  observations, the  highest score of the student was 90%. Thus, it was revealed that  task analysis could  increase the ability of the student  with light mental  retardation X to wash clothes in class IV/C1 of SLB Fanredha Padang. The researcher suggested to  the teachers to use  task analysis to help the students to wash their own clothes. Kata kunci: analysis tasks; Washing Clothes.